Effectiveness of Ivabradine in Treating Stable Angina Pectoris - Ye, Liwen (Medicine (Baltimore), 2016)
Many studies show that ivabradine is effective for stable angina. This meta-analysis was performed to determine the effect of treatment duration and control group type on ivabradine efficacy in stable angina pectoris. Relevant articles in the English language in the PUBMED and EMBASE databases and related websites were identified by using the search terms “ivabradine,” “angina,” “randomized controlled trials,” and “Iva.” The final search date was November 2, 2015. Articles were included if they were published randomized controlled trials that related to ivabradine treatment of stable angina pectoris. Patients with stable angina pectoris were included. The patients were classified according to treatment duration (<3 vs ≥3 months) or type of control group (placebo vs beta-receptor blocker). Angina outcomes were heart rate at rest or peak, exercise duration, and time to angina onset. Seven articles were selected. There were 3747 patients: 2100 and 1647 were in the ivabradine and control groups, respectively. The ivabradine group had significantly longer exercise duration when they had been treated for at least 3 months, but not when treatment time was less than 3 months. Ivabradine significantly improved time to angina onset regardless of treatment duration. Control group type did not influence the effect of exercise duration (significant) or time to angina onset (significant). Compared with beta-blocker and placebo, ivabradine improved exercise duration and time to onset of angina in patients with stable angina. However, its ability to improve exercise duration only became significant after at least 3 months of treatment.